Morphological and molecular based identification of Antifungal bacillus licheniformis (Mongolian Journal of Agricultural Sciences, 2017)
At present, plant diseases caused by soil borne plant pathogens have major constraints on crop production. Which include genera Fusarium spp, Phytophtora spp, Sclerotinia and Altenaria. Due to this reason, chemical fungicides are routinely used to control plant disease, which is also true in Mongolian case. However, use of these chemicals has caused various problems including environmental pollution with consequence of toxicity to human health also resistance of some pathogens to these fungicides are present. Fortunately, an alternative method to reduce the effect of these plant pathogens is the use of antagonist microorganisms. Therefore, some species of the genus Bacillus are recognized as one of the most effective biological control agent.Our research was focused to isolate Bacillus licheniformis, with antifungal potential, from indigenous sources. In the current study, 28 bacterial cultures were isolated from soil and fermented mare’s milk also named as koumiss. Isolated bacterial cultures were identified according to simplified key for the tentative identification of typical strain of Bacillus species. As a result 8 strains were positive and further screened for antifungal activity against Fusarium spp and Alternaria solani. Out of these 8 strains 5 strains are selected based on their high effectiveness against fungal pathogens and for further confirmation Polymerase Chain reaction run for effective bacterial strains using specific primers B.Lich-f and B.Lich-r.